PERAN MENGGAMBAR DALAM MEWUJUDKAN IDE KARYA ANIMASI - Dwi Waluyanto, Heru (Nirmana, 2001)
Animation had been known since 1940. Although obstructed by limited facilities and simple technologies%2C back then the Walt Disney had successfully produced animation masterpieces such as Pinocchio%2C Snow White%2C etc. In the world of animation%2C technology isnÂ’t the most important player%2C the one who plays the biggest role is the animator. A good animator should be competent in drawing / having good drawing skill. This competency is very important because a good animator is supposedly able to translate ideas in his / her mind into visual in the form of animated pictures. Abstract in Bahasa Indonesia : Animasi sudah dikenal sejak tahun 1940-an. Dengan teknologi yang masih sederhana pada waktu itu%2C Walt Disney antara lain memproduksi film-film masterpiece seperti Pinocchio dan Snow White. Dalam animasi bukan teknologinya yang terpenting%2C tetapi justru tenaga kerjanya (animator). Seorang animator harus memiliki kemampuan menggambar. Hal ini karena seorang animator dituntut mampu menterjemahkan sesuatu dalam pikiran menjadi wujud visual berupa gambar animasi. drawing%2C ideas%2C animation